2020
DOI: 10.1016/j.chempr.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Heterometallic Titanium-Organic Frameworks as Dual-Metal Catalysts for Synergistic Non-buffered Hydrolysis of Nerve Agent Simulants

Abstract: Heterometallic or mixed-metal Metal-Organic Frameworks (MOFs), incorporating two or more metal ions to the inorganic node of the frameworks, are increasingly gaining importance as a route to produce materials with increasing chemical and functional complexity. Heterometallic MOFs can offer important advantages over their homometallic counterparts to enable targeted modification of the adsorption properties, structural response, electronic structure or chemical reactivity of the framework. This field is still i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…This selective grafting of molecules to heterometallic clusters adds up to the pool of methodologies available for controlling the positioning and distribution of functional moieties in MOFs. We are confident the combined use of the empty space offered by these porous frameworks, alongside the different chemistries intrinsic to metal clusters and organic linkers, offers a promising playground for producing chemically complex environments by implantation of multiple components for unprecedented opportunities in synergistic phenomena [33] …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This selective grafting of molecules to heterometallic clusters adds up to the pool of methodologies available for controlling the positioning and distribution of functional moieties in MOFs. We are confident the combined use of the empty space offered by these porous frameworks, alongside the different chemistries intrinsic to metal clusters and organic linkers, offers a promising playground for producing chemically complex environments by implantation of multiple components for unprecedented opportunities in synergistic phenomena [33] …”
Section: Discussionmentioning
confidence: 98%
“…We have introduced here the first family of isoreticular titanium frameworks,MUV-10 and MUV-12, to demonstrate the ability of heterometallic Ti 2 Ca 2 clusters to direct the selective implantation of diamines to the soft Ca(II) sites in the inorganic node.T his results in the combination of Lewis acid Ti(IV) centers and available -NH 2 sites.C hemical modification of MUV-12-DAP with CH 3 Ie nables quantitative cycloaddition of CO 2 to propylene oxide at room temperature and atmospheric pressure for complete conversion in absence of additional co-catalysts and with excellent cyclability.T his selective grafting of molecules to heterometallic clusters adds up to the pool of methodologies available for controlling the positioning and distribution of functional moieties in MOFs.W eare confident the combined use of the empty space offered by these porous frameworks,a longside the different chemistries intrinsic to metal clusters and organic linkers,o ffers ap romising playground for producing chemically complex environments by implantation of multiple components for unprecedented opportunities in synergistic phenomena. [33] Angewandte Chemie Forschungsartikel…”
Section: Discussionmentioning
confidence: 99%
“…We have introduced here the first family of isoreticular titanium frameworks,MUV-10 and MUV-12, to demonstrate the ability of heterometallic Ti 2 Ca 2 clusters to direct the selective implantation of diamines to the soft Ca(II) sites in the inorganic node.T his results in the combination of Lewis acid Ti(IV) centers and available -NH 2 sites.C hemical modification of MUV-12-DAP with CH 3 Ie nables quantitative cycloaddition of CO 2 to propylene oxide at room temperature and atmospheric pressure for complete conversion in absence of additional co-catalysts and with excellent cyclability.T his selective grafting of molecules to heterometallic clusters adds up to the pool of methodologies available for controlling the positioning and distribution of functional moieties in MOFs.W eare confident the combined use of the empty space offered by these porous frameworks,a longside the different chemistries intrinsic to metal clusters and organic linkers,o ffers ap romising playground for producing chemically complex environments by implantation of multiple components for unprecedented opportunities in synergistic phenomena. [33]…”
Section: Discussionmentioning
confidence: 99%
“…56 While attempts to incorporate Mg 2+ to complete the series of alkaline Earth metals did not yield a crystalline product, a recent study demonstrated that the inclusion of Mg 2+ results in a separate MOF isostructural to the MIL-100 family. 57 We suspect that ionic radius is a critical determinant of isostructural MOF syntheses, given that the ionic radius for Mg 2+ in a six-coordinate geometry is 0.72 compared to Ca 2+ = 1.0, Mn 2+ = 0.83, Ba 2+ = 1.35, Sr 2+ = 1.18, and Cd 2+ = 0.95. 58 Interestingly, computational methods in the seminal report on MUV-10(Ca, Mn) predicted that an MUV-10(Cd) variant would be the least thermodynamically favorable, and yet we demonstrate it can be prepared following similar procedures.…”
Section: Preparation Of the Muv-10(m) Isostructural Seriesmentioning
confidence: 99%
“…The energetic degeneracy of the loose geometries could create a high density of mid-gap orbitals that would produce low-energy absorption, akin to Urbach tailing. 74,75 Although typically assumed to be crystalline, defects in MOFs, along with amorphous, liquid, and phase-change MOFs have attracted intense attention recently, 57,[76][77][78] and we propose that disorder near MOF nodes must be considered as well, especially to understand optical behavior.…”
Section: Ca Ca Ca Camentioning
confidence: 99%